Opinion 2458: Sphenopidae Hertwig, 1882 (Cnidaria, Anthozoa, Hexacorallia, Zoantharia): name conserved - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has conserved the usage of the family-group name Sphenopidae Hertwig, 1882 for a group of brachyneminic zoantharians over its rarely-used senior subjective synonym Palythoidae Duchassaing de Fombressin & Michelotti, 1860.
Keywords: Nomenclature; taxonomy; Cnidaria; Anthozoa; Hexacorallia; Zoantharia; Brachynemina; Palythoidae; Sphenopidae; Palythoa; Sphenopus; zoantharians; zoanthids; palytoxin; toxicology; Recent; worldwide